Pengaruh Kepuasan Kerja Dan Komitmen Afektif Terhadap Niat Berpindah PT. Charoen Pokphand Jaya Farm Mekarsari Kabupaten Sukabumi - Siti Nuraeni; Acep Samsudin; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of job satisfaction and affective commitment variables on turnover intention. The method used in this research is descriptive method and associative method with a quantitative approach. The population in this study are employees of PT. Charoen Pokphand Jaya Farm Mekarsari and the sample used was 55 respondents. The data technique used is multiple linear analysis and the sample technique uses a Likert scale. The results of this study indicate that the variables of job satisfaction and affective commitment have a positive and significant effect on turnover intention of 0.657. The results show that job satisfaction and affective commitment affect turnover intention by 65.7% and 34.2% is influenced by other factors outside this study. Based on the calculation results show multiple linear regression equations, as follows Y = 2.653 + 0.165X1 + 0.569X2 The regression coefficient is positive so it can be said that the direction of the influence of job satisfaction and affective commitment on intention to switch has a positive effect. Keywords: Job Satisfaction, Affective Commitment, Turnover Intention